3 x square - 4 x minus minus 7 splitting the middle term
Answers
Answered by
2
hi here is the solution
![3x ^{2} - 4x - 7 \\ = > 3x^{2} - 7x + 3x - 7 \\ = > x(3x - 7) + (3x - 7) \\ = > (x + 1)(3x - 7) 3x ^{2} - 4x - 7 \\ = > 3x^{2} - 7x + 3x - 7 \\ = > x(3x - 7) + (3x - 7) \\ = > (x + 1)(3x - 7)](https://tex.z-dn.net/?f=3x+%5E%7B2%7D++-+4x+-+7+%5C%5C++%3D++%26gt%3B+3x%5E%7B2%7D++-+7x+%2B+3x+-+7+%5C%5C++%3D++%26gt%3B+x%283x+-+7%29+%2B+%283x+-+7%29+%5C%5C++%3D++%26gt%3B+%28x+%2B+1%29%283x+-+7%29)
Similar questions